Accountability for the Crime of Theft Committed with Aggravation in Bandar Lampung (Study Decision Number 69/Pid.B/2023/PN.Tjk.) - Seregig, I Ketut; Ainita, Okta; Wahyu R, Amar (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The crime of theft with this aggravation is regulated in Article 363 of the Criminal Code with a maximum penalty of imprisonment of seven years. This act of theft is a type of theft that is different from other types of criminal acts of theft. Thus, aggravated theft is theft which basically contains elements of theft, and because of the addition of other elements, the risk of punishment becomes more severe. Aggravated theft is included in special theft because this theft is carried out in a certain way or under certain circumstances so that it is more serious.  In this case, the author takes an example of a criminal case of theft committed with aggravation in Bandar Lampung, which was committed by the defendant M. Ziaulhaq Adivar als Ezzi Adivar als MJ Bin Suhendra.